Analysis of definitive chemo-radiation outcomes in anal cancer: insights from a tertiary cancer center in the MENA Region - Alawabdeh, Tala; Abuhijlih, Ramiz; Mohamed, Issa; Alnasraween, Saif; Ababneh, Hazem; Turfa, Reem; Alsunna, Sanad; Khzouz, Yacoub; Abuhijla, Fawzi (Frontiers in Oncology, 2024)
Background: Outcomes of chemo-radiation (CRT) for anal cancer in Middle East and North Africa (MENA) are scarce. We aim to report treatment outcomes for anal cancer treated at tertiary cancer center in Jordan, with a particular focus on patients managed with non-oncological surgery prior definitive CRT.We conducted a retrospective review of patients diagnosed with locally advanced anal carcinoma who underwent definitive chemo-radiation at the King Hussein Cancer Center from 2007 to 2020. Patient demographics and disease characteristics were extracted, and a univariate chi-squared test was employed to assess the impact of chemotherapy type, HPV status, and pre-treatment non-oncological surgery on outcomes, including complete remission (CR), disease-free survival (DFS), and overall survival (OS).Kaplan-Meier tests were employed to analyze the obtained survival data.Results: Among the thirty-four initially identified patients, 30 were deemed eligible, with 24 (80%) achieving a complete response (CR). Notably, 21 patients (70%) tested positive for HPV, and 20 patients (95%) of them achieved CR, in contrast to only one patient (25%) of the 4 HPV-negative patients (p-value 0.006). The 5-year overall survival (OS) for HPVnegative patients was 25%, significantly lower than the 89% observed in HPV-positive patients (p-value = 0.001), with a median OS of 17 months for the former compared to not being reached for the latter. Regarding systemic therapy, in Group 1 where 23 patients received (5FU/Xeloda + Mitomycin), 74% achieved CR, while in Group 2 where 7 patients received (5 (FU/Xeloda + Cisplatin), all achieved CR (P value 0.3). The 5-year OS was 71% in Group 1 compared to 100% in Group 2, although the difference was not statistically significant (p-value = 0.14).Our strategy involving definitive chemoradiation for locally advanced anal cancer yielded oncological outcomes that align with findings reported in existing literature.The study did not reveal significant variations in outcomes based on the type of chemotherapy employed. However, it is important to note that larger-scale studies are essential to further validate and strengthen the robustness of our results.